ANALISIS POWER BUDGET PADA PERANCANGAN JARINGAN AKSES FIBER TO THE HOME (FTTH) PADA PERUMAHAN D'EAST TOWNHOUSE CIMANGGIS - Alfito Danies Widayadi (2023)
D'East Townhouse Cimanggis Housing is a gated community currently under construction. The author plans to design a Fiber To The Home (FTTH) network using GPON technology. The feasibility of data transmission quality from the service provider to the customer's home is assessed by evaluating the electricity budget parameter. In this study we analyze the calculated values manually and the results of design simulation measurements with the OptiSystem software from OLT over ONT to nearest, middle and farthest distances with different splitter designs on ODP (splitter 1:4, 1:8, 1:16, 1:32) to determine which design has the best received power quality. The power budget value from calculations and simulations determined for the farthest downstream link with a 1:4 ODP splitter is -21,718 dBm calculation, -21,711 dBm simulation; Splitter 1:8 from -24.284 dBm calculation, -24.055 dBm simulation; 1:16 splitter with -27,993 dBm calculation, -26,638 dBm simulation; Splitter 1:32 from -31.351 dBm calculation, -30.321 dBm simulation. The values determined by calculations and simulations provide almost the same results and do not show any major difference. The results of the analysis of the power budget values show that the design with an ODP splitter 1:4 has the best received power quality and can be implemented compared to other splitters